Bretón, Jiménez Delgado and Nieto: a triad of Masonic musicians during the Restoration - Anaya-Gámez, Fernando M. (2026)
The R. L. M. Fraternidad Ibérica n. 90 of the Grande Oriente Nacional de España, led by Eduardo Caballero de Puga, was an influential association that united some leading members of Madrid's Restoration society. A proponent of cultural and educational projects, it was also the lodge with the largest number of musicians of its era, including three distinguished figures: Tomás Bretón, F. Javier Jiménez Delgado, and Manuel Nieto. This study aims to shed light on aspects of their Masonic trajectories and their unwavering commitment to the institution's principles in which they were initiated.